Highly stable Delta-Sigma Modulator for industrial applications - Diwakar, K.; Senthilpari, C.; Singh, Ajay Kumar (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2008)
A higher order Delta Sigma Modulator (DSM) is basically an unstable system. The approximate conditions for stability cannot be used for the design of a DSM for industrial applications where risk is involved. The existing second order, single stage, single bit, unity or non unity feedback gain (k), discrete DSM cannot be used for the full range (-k to +k) of an input signal since the DSM becomes unstable when the input signal is above +/- 0.7 k. In the present paper, a second order, single stage, discrete DSM with input signal dependant feedback gain and an input signal dependant DSM operating period is proposed. The proposed DSM can operate with a wide range of input signals without causing instability.